2018
DOI: 10.1080/15476286.2018.1526539
|View full text |Cite
|
Sign up to set email alerts
|

Identification of factors that promote biogenesis of tRNACGASer

Abstract: A wide variety of factors are required for the conversion of pre-tRNA molecules into the mature tRNAs that function in translation. To identify factors influencing tRNA biogenesis, we previously performed a screen for strains carrying mutations that induce lethality when combined with a sup61-T47:2C allele, encoding a mutant form of . Analyzes of two complementation groups led to the identification of Tan1 as a protein involved in formation of the modified nucleoside N4-acetylcytidine (ac4C) in tRNA and Bud13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…To analyze the nucleoside composition of total tRNA, the tRNA was isolated from exponentially growing cultures at OD 600 ≈0.8 [21]. The tRNA was digested to nucleosides using nuclease P1 (Sigma-Aldrich, N8630) and bacterial alkaline phosphatase (Sigma-Aldrich, P4252) and the hydrolysate analyzed by HPLC [71, 72]. The compositions of the elution buffers were as described [72] with the difference that methanol concentration in buffer A was changed to 5% (v/v).…”
Section: Methodsmentioning
confidence: 99%
“…To analyze the nucleoside composition of total tRNA, the tRNA was isolated from exponentially growing cultures at OD 600 ≈0.8 [21]. The tRNA was digested to nucleosides using nuclease P1 (Sigma-Aldrich, N8630) and bacterial alkaline phosphatase (Sigma-Aldrich, P4252) and the hydrolysate analyzed by HPLC [71, 72]. The compositions of the elution buffers were as described [72] with the difference that methanol concentration in buffer A was changed to 5% (v/v).…”
Section: Methodsmentioning
confidence: 99%
“…In budding yeast, only 5% of protein‐coding genes contain introns (Spingola et al ., ). Consistent with this, only a few genes with abnormal mRNA splicing, including TAN1 , MER1 and MATa1 , have been identified in the yeast bud13 ⊿ mutant cells (Scherrer and Spingola, ; Tuo et al ., ; Zhou et al ., ; Xu et al ., ). By contrast, most protein‐coding genes in higher eukaryotes harbor introns.…”
Section: Discussionmentioning
confidence: 97%
“…In the absence of Bud13p, the splicing efficiency of reporter constructs is substantially decreased both in vivo and in vitro (Gottschalk et al ., ; Dziembowski et al ., ). So far, the splicing of four pre‐mRNAs, Actin , TAN1 , MER1 and MATa1 , has been demonstrated to be controlled by Bud13p (Clark et al ., ; Khanna et al ., ; Zhou et al ., ; Wysoczanski and Zweckstetter, ; Xu et al ., ). Additionally, Bud13p has been shown to function in the formation of spliceosome and activation of the B complex (Deckert et al ., ; Bessonov et al ., ; Bao et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The presence of dihydrouridine influences D-loop structure by promoting the formation of a hairpin with a stable stem and flexible loop and facilitates tertiary interactions that contribute to three-dimensional tRNA folding (123). In budding yeast, strains with mutations in Dus2, which modifies U20, have been shown to have reduced levels of a mutant allele of tRNA Ser-CGA, suggesting a role for D modification in imparting tRNA stability (124). Recent studies investigating the role of human DUS proteins have shown that although D is abundant across many tRNAs, only a subset of tRNA species show impaired expression levels upon DUS enzyme depletion (89).…”
Section: Discussionmentioning
confidence: 99%